Morphometric Predictors of Morbidity after Pancreatectomy. Issue 12 (December 2016) - Jaap, Kathryn; Hunsinger, Marie; Dove, James; Mcginty, Katrina; Stefanowicz, Edward; Fera, Jillian; Wild, Jeffrey; Shabahang, Mohsen; Blansfield, Joseph
Pancreatic surgery has historically been associated with high morbidity and mortality. One model that could predict outcomes is the assessment of preoperative morphometrics. The objective of this study was to compare different clinical and morphometric features of patients undergoing pancreatectomy to predict morbidity. This is a retrospective chart review of patients undergoing pancreatectomy from December 2004 to October 2013. Morphometric parameters on preoperative CT scans were measured and patients were grouped to examine their association with postoperative morbidity. A total of 180 patients were included in this study (90 males and 90 females). At the time of diagnosis, patients had an average age of 66.7 years (range = 24–90), and median body mass index of 27.4 kg/m 2 (range = 16–58 kg/m 2 ). Sixty-one patients (33.9%) experienced surgical complications. Of the individual morphometric variables examined, sarcopenia was the best predictor of length of stay and surgical complications. On multivariate analysis, there was a strong statistically significant correlation of sarcopenia with surgical complications (odds ratio = 3.524, P = 0.0049). No other morphometric variables predicted morbidity. Sarcopenia is a useful predictor for postoperative morbidity after pancreatectomy. The results of this study suggest that noninvasive preoperative testing can be used to quantify postoperative complications after pancreatic surgery.